Pengaruh Frekuensi Penyiangan dan Sistem Budidaya terhadap Keberadaan Gulma Ludwigia octovalvis, Pertumbuhan dan Hasil Padi Sawah - Ade Riska Nuraeni; Jenal Mutakin; Resti Fajarfika (Fakultas Pertanian - UMJ, 2026)
Rice (Oryza sativa L.) is a major staple food commodity in Indonesia; however, its productivity often declines due to weed competition, one of which is Ludwigia octovalvis, commonly found in flooded paddy fields. Weed control through weeding practices and the application of appropriate cultivation systems is an important factor in improving rice growth and yield. This study aimed to determine the effects of weeding frequency and cultivation systems on the presence of Ludwigia octovalvis, as well as on the growth and yield of lowland rice. The research was conducted from July to October 2024 using an experimental method with a split-plot design. Conventional cultivation and no-tillage (NT/TOT) systems were used as main plots, while weeding frequency served as subplots, consisting of no weeding (P0), one weeding (P1), two weedings (P2), and three weedings (P3). The results showed that Ludwigia octovalvis began to appear at 60 days after transplanting and did not exhibit significant differences among treatments. The cultivation system and weeding frequency had no significant effect on plant height and tiller number at the early growth stage; however, treatment interactions significantly affected the number of productive tillers. The weight of harvested dry grain did not differ significantly among treatments. Therefore, weeding frequency plays an important role during the vegetative phase, whereas the final rice yield is more strongly influenced by environmental factors and integrated crop management.